Clinical characteristics and rehabilitation potential in children with cerebral palsy based on MRI classification system - Yang, Jie; Chen, Congjie; Chen, Ningning; Zheng, Helin; Chen, Yuxia; Li, Xiaoli; Jia, Qingxia; Li, Tingsong (Frontiers in Pediatrics, 2024)
Background The correlation of clinical characteristics of cerebral palsy (CP) and the magnetic resonance imaging classification system (MRICS) for (CP) is inconsistent. Specifically, the variance in rehabilitation potential across MRICS remains underexplored. Aims To investigate the clinical characteristics and potential for rehabilitation in children with CP based on MRICS. Materials and methods Children with CP admitted to the Department of Rehabilitation, Children's Hospital of Chongqing Medical University between 2017 and 2021 were included in the study. Qualified cases underwent a follow-up period of at least one year. The clinical characteristics of CP among different MRICS were analyzed, then the rehabilitation potential was explored by a retrospective cohort study. Results Among the 384 initially enrolled children, the male-to-female ratio was 2.3:1, and the median age of diagnosis was 6.5 months (interquartile range: 4–12). The most prevalent MRICS categorization was predominant white matter injury (40.6%), followed by miscellaneous (29.2%) and predominant gray matter injury (15.6%). For the predominant white matter injury and miscellaneous categories, spastic diplegia emerged as the leading subtype of CP, with incidences of 59.6% and 36.6%, respectively, while mixed CP (36.7%) was the most common type in children with predominant gray matter. Notably, 76.4% of children with predominant white matter injury were classified as levels I–III on the gross motor function classification system (GMFCS), indicating significantly less severity than other groups (χ2 = 12.438, p = 0.013). No significant difference across MRICS categories was observed for the manual ability classification system (MACS) (H = 8.176, p = 0.085). Rehabilitation potential regarding fine motor function and adaptability based on Gesell assessment was dependent on MRICS over the follow-up period. Children with normal MRI scans exhibited superior rehabilitation outcomes. Commencing rehabilitation at an earlier stage produced consistent and beneficial results in terms of fine motor function and adaptability across all MRICS categories. Moreover, participants below 2 years of age demonstrated enhanced rehabilitation potential regarding fine motor outcomes and adaptability within the MRICS framework. Conclusion MRICS displayed a significant association with clinical characteristics and rehabilitation efficacy in children with CP.